Phenomena identification and ranking table study for thermal hydraulics for Advanced High Temperature Reactor. (February 2019) - Lin, Hsun-Chia; Zhang, Sheng; Diamond, David; Bajorek, Stephen; Christensen, Richard; Guo, Yujun; Yoder, Graydon; Shi, Shanbin; Lv, Qiuping; Sun, Xiaodong
Abstract: The Advanced High Temperature Reactor (AHTR) is a conceptual design of a Fluoride salt-cooled High-temperature Reactor (FHR) utilizing 7 LiF-BeF2 (66–34 mol%) as its primary coolant. To identify key phenomena that impose potential challenges on thermal hydraulics modeling and simulation of such a reactor system, a thermal hydraulics phenomena identification and ranking table (TH-PIRT) study was performed for the AHTR in a Department of Energy Nuclear Energy University Program (NEUP) integrated research project led by Georgia Institute of Technology. A panel of experts from regulators, industries, national laboratories, and academia was assembled for the study. In this paper, the TH-PIRTs identified by the panel for two events, namely, station blackout and simultaneous withdrawal of all control rods, are summarized and discussed in detail. In addition, the key phenomena that warrant further study and research for AHTR analysis are identified to support the validation of thermal hydraulics system-level analysis codes and computational fluid dynamics simulation tools, as well as future FHR reactor licensing.